Sodium‐glucose cotransporter‐2 inhibitors and the risk of gout: A Danish population based cohort study and symmetry analysis. Issue 10 (13th May 2021) - Lund, Lars Christian; Højlund, Mikkel; Henriksen, Daniel Pilsgaard; Hallas, Jesper; Kristensen, Kasper Bruun
Abstract: Purpose: Sodium‐glucose cotransporter‐2 inhibitors (SGLT2‐I) are frequently used in type 2 diabetes and have recently been associated with lower rates of gout compared to glucagon‐like peptide‐1 receptor agonists (GLP1‐RA). Our objective was to assess the association between SGLT2‐I initiation and gout using a cohort study design and a symmetry analysis. Methods: Using the Danish nationwide health registries, we conducted an active comparator, new user cohort study comparing the 3‐year risk of gout among SGLT2‐I users with propensity score matched GLP1‐RA users. Individuals were followed according to the intention‐to‐treat, and incidence rate differences (IRD) and hazard ratios (HR) were obtained. To address unmeasured confounding that is stable over time, a corresponding symmetry analysis was performed. Results: 11 047 pairs of SGLT2‐I and GLP1‐RA users were identified, contributing 42 201 person‐years of follow‐up. The incidence rate of gout was 4.1 and 7.0 events per 1000 person years among SGLT2‐I and GLP1‐RA users, yielding an IRD of −3.0 (95% confidence interval: −4.4 to −1.5) and HR of 0.58 (0.44 to 0.75). In the symmetry analysis, 80 individuals initiated SGLT2‐Is prior to gout; 118 patients initiated treatment after gout. The trend adjusted SR was 0.63 (0.47 to 0.84) and the active comparator adjusted estimate was 0.67 (0.44 to 0.86). Conclusions: Initiation of SGLT2‐Is was associated with a markedly decreased risk of gout compared to initiation of GLP1‐RAs. The findings are comparable to prior studies addressing this association.